Kinerja Usahatani Asparagus di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - DARMAWAN, I MADE DODY; WIDYANTARA, I WAYAN; AGUNG, DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Asparagus Farm Performance in Pelaga Village , Petang District, Badung Regency . Asparagus farm including a newly developed farming in Bali . The purpose of this study was to determine the allocation of the costs of the farm asparagus , and how the performance of asparagus farming in Pelaga village , Petang District, Badung Regency in terms of BEP analysis and DOL. Costs necessary for the asparagus farming is quite high , Rp. 28.310,00 for a year . Results of the BEP analysis showed that farming asparagus is able to provide benefits to farmers , where the selling price per kg of asparagus in the market (Rp. 28.310.00 ) greater than the BEP selling price (Rp. 17.625,00 ) and the price per kg in the market is stable because there was no change to the current price. In terms of quantity , the quantity sold farmers still higher ( 1.420 kg / year ) of the BEP quantity ( 381  kg / year ) with an average land area of ??15 acres. DOL analysis value of 1,37 shows that farm profits will continue to grow in line with increased production in which every 10 % increase in production will drive the gain of 13,7 %. Asparagus farming is very promising views of BEP analysis and DOL , but in the field there are many farmers experiencing farm constraints , government assistance and mertanadi koperasi particularly needed to assist both in terms of production facilities and technical farming and land development asparagus very well done to make a point higher profits for farmers. Keywords: Asparagus Farm Performance, Analysis of BEP, Analysis of DOL